Cytomixis doesn’t induce obvious changes in chromatin modifications and programmed cell death in tobacco male meiocytes - Mursalimov, Sergey; Permyakova, Natalya; Deineko, Elena; Houben, Andreas; Demidov, Dmitri (Frontiers in Plant Science, 2015)
Cytomixis is a poorly studied process of nuclear migration between plant cells. It is so far unknown what drives cytomixis and what is the functional state of the chromatin migrating between cells. Using immunostaining, we have analyzed the distribution of posttranslational histone modifications (methylation, acetylation, and phosphorylation) that reflect the functional state of chromatin in the tobacco microsporocytes involved in cytomixis. We demonstrate that the chromatin in the cytomictic cells does not differ from the chromatin in intact microsporocytes according to all 14 analyzed histone modification types. We have also for the first time demonstrated that the migrating chromatin contains normal structures of the synaptonemal complex and lacks any signs of apoptosis. As has been shown, the chromatin migrating between cells in cytomixis is neither selectively heterochromatized nor degraded both before its migration to another cell and after it enters a recipient cell as micronuclei. We also showed that cytomictic chromatin contains marks typical for transcriptionally active chromatin as well as heterochromatin. Moreover, marks typical for chromosome condensation, synaptonemal complex formation and key proteins required for the formation of bivalents were also detected at migrated chromatin.